A convergência no radiojornalismo : uma análise das transmissões da rádio Jovem Pan de São Paulo através do facebook - Bertoncello, Marcos Notari (2019)
Through the traditional press vehicles’s immersion into the world of the internet, in what Jenkins (2009) conceptualizes of convergence culture, a new challenge for the radio was again discussed, as well as at the time of the emergence and strengthening of television in the decades 1950s and 1960s. The consolidation of social networks exposes radio as an obsolete medium, which uses the audio to broadcast its messages, so it must reinvent itself in the face of the possibilities of a multiplatform narrative. Thus, some broadcasters have sought a new tool, Facebook and its audiovisual broadcasts, and such appropriation has affected the radio language and therefore the work of the journalist and the view of the audience. The research that follows has the objective to examine the Radio Jovem Pan’s transmissions, of the city of São Paulo, through the powerful social network Facebook. For that, the corpus of research was divided into two programs of the transmitter to be analyzed: Jornal Jovem Pan and 3 em 1, both transmitted in video on the Internet. It has been observed that, based on the plan adopted by Jovem Pan to carry out online transmissions of its programming, the visual references can mean communication noises for the traditional radio audience, since it conflicts with two human senses: seeing and listening. The theoretical framework is embodied in Henry Jenkins' theory on media convergence, participatory culture, and collective intelligence.